A coalitional control scheme with applications to cooperative game theory. (12th September 2013) - Maestre, J.M.; Muñoz de la Peña, D.; Jiménez Losada, A.; Algaba, E.; Camacho, E. F.
SUMMARY In this paper, we present a control scheme in which a set of agents switches between different network topologies in order to regulate a set of unconstrained linear systems. The problems of how to decide the time‐varying communication strategy and the corresponding control strategies are addressed. A design method that guarantees closed‐loop stability for the proposed scheme is also provided. In addition, the network topology optimization problem is posed as a cooperative game, so that tools from game theory can be used to study the relevance of the different links and the agents. Finally, the proposed scheme is illustrated through a simulation example. Copyright © 2013 John Wiley & Sons, Ltd.